The Anatomy Heresies - Shively, M. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
This essay presents incorrect, misleading, or easily misconstrued anatomical statements from a number of sources and follows each with editorial and clinically applicable commentary. The purpose of this exercise is not to degrade the sources, but only to correct the misconceptions in an attempt to avoid their perpetuation.
Keywords: Dog; anatomy; bone; joint; horse